2018
DOI: 10.1111/dme.13813
|View full text |Cite
|
Sign up to set email alerts
|

‘It's an important part, but I am not quite sure that it is working’: educators’ perspectives on the implementation of goal‐setting within the ‘DAFNE’ diabetes structured education programme

Abstract: While educators saw benefits in the implementation of goal-setting and planning strategies within diabetes self-management education, concerns about how well goal-setting currently fits within diabetes self-management education and follow-up care were evident. Additionally, many educators experienced the delivery of goal-setting and action-planning strategies as challenging and would value additional training opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…Importantly, although outcome (weight) measurement frequently happened in the intervention sessions and were fed back to participants, they were not often reviewed with participants so they could modify their goals in light of failure or success. Similar underdelivery of self-regulation techniques such as goal setting and action planning has been noted in other studies [ 27 ]. Other BCTs that were underdelivered by all providers were those that involved monitoring behavior such as via diaries or pedometers without feedback, prompting consideration of pro’s and con’s, and providing emotional social support.…”
Section: Discussionsupporting
confidence: 76%
“…Importantly, although outcome (weight) measurement frequently happened in the intervention sessions and were fed back to participants, they were not often reviewed with participants so they could modify their goals in light of failure or success. Similar underdelivery of self-regulation techniques such as goal setting and action planning has been noted in other studies [ 27 ]. Other BCTs that were underdelivered by all providers were those that involved monitoring behavior such as via diaries or pedometers without feedback, prompting consideration of pro’s and con’s, and providing emotional social support.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, discussing goals in the groups may be helpful not only to increase accountability but also to provide feedback on the quality of action plans. However, facilitators too may find goal setting and action planning challenging and may need more specific training on it (Fredrix, Byrne, Dinneen, & McSharry, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While HCPs generally recognise the importance of providing psychological and social support for adults with diabetes, 14 15 studies have reported minimal inclusion of such issues in routine diabetes care due to lack of training, tools and skills to engage in conversations about psychological and social aspects. [16][17][18] Furthermore, access to specialist psychology services is limited in most areas. Structural barriers such as consultation time constraints due to a focus on fulfilling the requirements set by clinical guidelines and an emphasis on glucose targets also limit the capacity for psychological and social support.…”
Section: Introductionmentioning
confidence: 99%